Investigation the effects of 6 weeks pilates exercises on biomotorical variables and self-esteem scores of young women - Ozhan Bavlı; Ozlem Koybası (Selcuk University, 2016)
Purpose of this study was the investigate the effects of six weeks mat based pilates exercise on biomotirical variables and self esteem of young women. Totally 22 women (mean age;  20.1±2.2 year) participated in to the study voluntary. Participants divided into the two groups (pilates:10, control: 12) randomly. Pilates group did pilates exercise for six weeks. Control group did nothing. Pretests and post tests measurements of body height, body weight, flexibility, balance, abdominal strength and self esteem performed. SPSS used for analysis. Analysis showed that there were statistical findings (p lt;0.05) on pretest and post test measurements of pilates group of flexibility, abdominal strength, and self esteem variables (p lt;0.05). When comparison the measurement  pretest and post test  differences of two groups, there was a statistical differences about flexibility, balance, and abdominal strength. According to findings it is possible to say that six weeks of pilates exercise is the proper exercise type for young girls. Also it can be advice that  for positive effecting to self esteem pilates works were preferable exercise methods for young women.